2021
DOI: 10.3390/rs13132606
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Water Infiltration Rate Using Ground and UAV Hyperspectral Data: A Case Study of Alento, Italy

Abstract: Water infiltration rate (WIR) into the soil profile was investigated through a comprehensive study harnessing spectral information of the soil surface. As soil spectroscopy provides invaluable information on soil attributes, and as WIR is a soil surface-dependent property, field spectroscopy may model WIR better than traditional laboratory spectral measurements. This is because sampling for the latter disrupts the soil-surface status. A field soil spectral library (FSSL), consisting of 114 samples with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…(2) Francos et al found that the traditional field non-imaging spectral data ar discrete and easily affected by the soil background [50], while the ground hyperspectr…”
Section: Discussionmentioning
confidence: 99%
“…(2) Francos et al found that the traditional field non-imaging spectral data ar discrete and easily affected by the soil background [50], while the ground hyperspectr…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with published works, the presented results provide a comparable estimate of the observed characteristics of soil hydraulic properties, e.g., Ambrosone et al [39] report R 2 = 0.73 for the linear method to determine soil water content, using multispectral data from the Sentinel 2 satellite and the OPTRAM model [117], and R 2 = 0.8 for the nonlinear method. Francos et al [33] performed a detailed analysis of the spectral characteristics of soils in relation to the infiltration rate. The results showed a very good agreement between laboratory and spectral data; however, the result varied according to the different types of soils and their physical properties.…”
Section: Estimation Of K S and Fwc Data From Aerial Imagingmentioning
confidence: 99%
“…The present method eliminates some of the limitations of the above approaches. In monitoring soil without vegetation cover using optical spectral data, the structural properties of soils and the content of color elements, such as hematite or goethite, can play an important role, which can significantly affect the spectral information [33]. Evaluation of soil hydraulic properties using spectral vegetation indices (e.g., the RGB index, [27]) may have only a limited possibility to identify short-term changes in the stand water regime.…”
Section: Estimation Of K S and Fwc Data From Aerial Imagingmentioning
confidence: 99%
See 2 more Smart Citations